Effect of Long-Distance Running on Inter-segment Foot Kinematics and Ground Reaction Forces: A Preliminary Study - Li, Jialin; Song, Yang; Xuan, Rongrong; Sun, Dong; Teo, Ee-Chon; Bíró, István; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2022)
Long-distance running has gained huge popularity in recent years, yet the intra-foot adaptations during this event remain unclear. This study aimed to examine the kinematic and ground reaction force (GRF) alterations induced within the foot following a 5 km and 10 km running using Oxford Foot Model (OFM). Ten marathon-experienced recreational runners participated in this study. Five-kilometer running led to more rearfoot dorsiflexion, rearfoot eversion, and rearfoot rotation while less forefoot plantarflexion during the stance phase. Increased rearfoot plantarflexion, while decreased forefoot plantarflexion, supination, adduction, as well as hallux plantarflexion, was observed at 10 km. In addition, forefoot space of footwear was found to play a role in hallux kinematics. Concerning GRFs, lesser propulsive force was presented after 10 km running. Findings of this study showed excessive foot motion at 5 km while changed foot posture and decreased propulsive force at 10 km of running, which may potentially increase the risks of running-related injuries (RRI) due to overuse and/or fatigue. Nevertheless, further research is warranted, and this study could be used as a preliminary reference to evaluate and predict foot RRI.